Utilization of Jenitri as A Bioadsorbent in Petroleum Field-Produced Water - Muhammad Khairul Afdho; Rika Lala Saputri; Adiella Zakky Juneid; Razif Muhammed Nordin; Muhammad Salihin Bin Zakaria; Tomi Erfando (Scientific Contributions Oil and Gas, 2025)
As oil and gas fields mature, the volume of produced water can increase substantially, often exceeding 90% of total production. This water cannot be directly discharged or reused due to harmful contaminants that pose considerable environmental risks. One major challenge is the absence of efficient, eco-friendly, and cost-effective filtration media for its treatment. This study aimed to develop and assess an alternative adsorbent derived from jenitri seeds, chemically activated with potassium hydroxide (KOH) at controlled temperatures. The primary goal was to identify a more effective and sustainable adsorbent than those currently used in oilfield operations. The methodology involved the preparation of this adsorbent, Its physicochemical characterization included bulk density measurement, scanning electron microscopy (SEM), and Fourier transform infrared spectroscopy (FTIR) analyses, along with performance testing through filtration, benchmarked against natural adsorbents such as candlenut and walnut. The KOH-activated jenitri demonstrated superior pollutant removal performance, primarily due to enhanced porosity and surface area resulting from the activation process. It exhibited the lowest bulk density (0.6 g/mL), an optimal porous structure as revealed by SEM, and the presence of active functional groups such as –OH, C=O, and C–O, identified through FTIR analysis. In filtration tests, KOH-activated jenitri effectively reduced total dissolved solids (TDS) to 600 mg/L and turbidity to 100–200 nephelometric turbidity units (NTU), outperforming natural jenitri, candlenut, and walnut, whose limited porosity contributed to lower adsorption efficiency